Stimulated coherent Smith-Purcell radiation - Aleinik A. N.; Aryshev A. S.; Bogomazova E. A.; Kalinin B. N.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Saruev G. A.; Sharafutdinov A. F. (2004, 2004)
The designing of free electron lasers (FEL) on the basis of undulators in a submillimeter wavelength range concerns with problems of manufacture of undulators with a very small period. Also accelerators with high energy of an electron beam (> 50 MbepsiB) is required for this purpose. It is necessary to take into account that in such devices the precise and expensive magnetic systems are used. In a number of works the alternate mechanism of FEL, based on use of Smith-Purcell radiation (SPR) was considered. For realization of feedback in such FEL it is necessary to use new type of the resonator. The results of experimental investigation of stimulated coherent SPR (CSPR) using the transverse resonator are presented.